Couple therapy for depression : a clinician's guide to integrative practice - Hewison, David; Clulow, Christopher F.; Drake, Harriet (Oxford University Press, 2014)
Depression is second after heart disease as the most damaging health condition in the world. The NHS has devoted huge resources to training thousands of psychological therapists to work in 'Improving Access to Psychological Therapies' services specifically to treat depression in adults and couple therapy has been identified as one of the effective ways of treating it. Couple Therapy for Depression is an integrative 20-session couple therapy designed to treat depression in couples where there is also relationship distress. Following the recommendations of the UK's National Institute for Clinica.